(untitled) (Biological Sciences - PJSIR, 2020)
The electrochemical reduction of 4-(3-pyridylazo)-3-amino-2-pyrazolin-5-one in universal buffer solutions of different pH values was studied at 268 K. From the results obtained, it was concluded that the azo compound was reduced via an ECEC mechanism (two-electron and two-proton mechanism). The mechanism was confirmed by digital simulation. The heterogeneous electron transfer